(untitled) (Contemporary Mathematics, 2021)
By means of the linearization method, a nonterminating exotic 3F2-series with five free integer parameters is reduced to particular instances of a known Ω (x, y) function. With a help of the Kummer and Thomae transformations, ten large classes of 3F2-series are evaluated in terms of π, and log(1+). A collection of 700 elegant summation formulae is presented.